Designing connected products : UX for the consumer Internet of things - Rowland, Claire; Charlier, Martin; Light, Ann (Ann Maxine), 1961-; Lui, Alfred, 1973-; Goodman, Elizabeth, 1976- (Sebastopol : O'Reilly, 2015)
Networked thermostats, fitness monitors, and door locks show that the Internet of Things can (and will) enable new ways for people to interact with the world around them. But designing connected products for consumers brings new challenges beyond conventional software UI and interaction design. This book provides experienced UX designers and technologists with a clear and practical roadmap for approaching consumer product strategy and design in this novel market. By drawing on the best of current design practice and academic research, Designing Connected Products delivers sound advice for working with cross-device interactions and the complex ecosystems inherent in IoT technology.
What's different about user experience design for the internet of things? -- Things : the technology of connected devices -- Networks : the technology of connectivity -- Case study 1: Proteus Digital Health : the connected pill -- Product/service definition and strategy -- Understanding people and context -- Translating research into product definitions -- Case study 2: Little Kelham : connected home -- Embedded device design -- Interface and interaction design -- Case study 3: Ford SYNC 3 : connected car -- Cross-device interactions and interusability -- Interoperability -- Case study 4: LOOP : connected pelvic floor exerciser -- Responsible IoT design -- Supporting key interactions -- Case study 5: BRCK : rugged portable WiFi hotspot -- Designing with data -- Iterative design : prototyping and learning -- Designing complex, interconnected products and services.
Includes bibliographical references and index.
Keywords: Graphical user interfaces (Computer systems); Ubiquitous computing; Internet of things; User-centered system design; Human-computer interaction